Increasing the competitiveness of Rural Banks through an innovation approach in Bogor District - Dimas Ari Darmantyo; Ratno Ratno; Yustiana Wardhani (The Management Journal of Binaniaga, 2020)
Competition in the banking world in increasing the value of its assets is getting tighter.The presence of financial technology adds to the tight competition in the banking world. Rural Banks (BPR) which focuses on small community services and MSMEs must innovate in order to survive in the banking industry. This research aims to find out if there is an influence of product innovation, process innovation, marketing innovation and organizational innovation on business performance, with accidental sampling method to obtain 150 samples of BPR Customers Bogor District, this research uses Structural Equation Modelling (SEM) method to analyze the data obtained. The results showed that, there is a positive influence of product innovation, process innovation, marketing innovation and organizational innovation on business performance. Product innovation variables have a stronger impact on business performance than marketing innovation, organizational innovation and process innovation. Keywords : Product Innovation, Process Innovation, Marketing Innovation and Business Performance